Essential Content for Discharge Instructions in Pediatric Emergency Care: A Delphi Study. Issue 5 (May 2018) - Curran, Janet A.; Murphy, Andrea; Burns, Emma; Plint, Amy; Taljaard, Monica; MacPhee, Shannon; Fitzpatrick, Eleanor; Bishop, Andrea; Chorney, Jill; Bourque, Megan
Abstract : Objective: The aim of this study was to identify the 5 most essential discharge instruction content elements that should be communicated to all caregivers of children who present to the emergency department (ED) with asthma, vomiting/diarrhea, abdominal pain, fever, minor head injury, or bronchiolitis. Methods: A discharge information content list was developed for each illness presentation following a review of the literature. Using a modified Delphi technique, 6 lists were distributed to a panel of experts from EDs across Canada using a secure online survey tool with the goal of achieving the 5 most essential discharge instruction elements. Results: A total of 37 emergency clinicians completed all 4 rounds of the Delphi. Consensus for the final 30 content items ranged from 51.4% to 100%. Items pertaining to diarrhea/vomiting, abdominal pain, fever, and bronchiolitis obtained relatively high levels of consensus for all top 5 items. The majority of items (n = 19 [63.3%]) that reached consensus across the illness presentations were associated with instructions intended to educate caregivers on instances when they should return to the ED department. Conclusions: Findings from this study provide a better understanding of what should be communicated to caregivers of children who present to the ED with a number of different illness presentations. Results from this study suggest that health care providers agree on the importance of providing information to caregivers regarding when to return to the ED with their child. Reaching consensus among all experts in this study provides insight into the difficulty of standardizing discharge communication in the absence of widely accepted guidelines.